2010
DOI: 10.1002/jbm.b.31662
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial effect of polyethyleneimine nanoparticles incorporated in provisional cements against Streptococcus mutans

Abstract: Incorporation of nanoparticles may prevent caries and inflammation, and thereby improve the results of the prosthetic treatment. Further investigation is necessary on the effect on mechanical properties and clinical relevance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
30
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(30 citation statements)
references
References 11 publications
0
30
0
Order By: Relevance
“…,b, Shvero et al . ). A recent study evaluated the effects on a clinical strain of Enterococcus faecalis of two endodontic sealers (AH Plus and GuttaFlow) incorporating low concentrations of insoluble antibacterial QPEI nanoparticles (Kesler‐Shvero et al .…”
Section: Introductionmentioning
confidence: 97%
“…,b, Shvero et al . ). A recent study evaluated the effects on a clinical strain of Enterococcus faecalis of two endodontic sealers (AH Plus and GuttaFlow) incorporating low concentrations of insoluble antibacterial QPEI nanoparticles (Kesler‐Shvero et al .…”
Section: Introductionmentioning
confidence: 97%
“…It has a strong permeabilizing effect but no bactericidal effect on gram-negative bacteria [13]. PEI prepared in nanoparticles was incorporated in dental provisional cements and found to had antibacterial effect against Streptococcus mutans [14]. Insoluble crosslinked quaternary ammonium polyethylenimine (PEI) nanoparticles incorporated at 1 or 2% w/w in a resin composite also have an antimicrobial effect against Staphylococcus aureus, Staphylococcus epidermidis, Enterococcus faecalis, Pseudomonas aeruginosa and Escherichia coli [15].…”
Section: Introductionmentioning
confidence: 99%
“…PEI nanoparticles could be immobilized in resin-based materials to exert a strong antibacterial effect without the leachout of the nanoparticles, thus preserving the antibacterial activity and mechanical properties for potential dental applications [40]. The antibacterial effects of using PEI nanoparticles at 0.5, 1 and 2% by mass in a provisional cement were studied in vitro against S. mutans and Enterococcus faecalis [86]. The results indicated that the minimum effective concentration should be 1% of PEI nanoparticles to ensure a proper antibacterial activity for the dental cement [86].…”
Section: Other Studies Using Nanotechnology To Tackle Oral Biofilms Andmentioning
confidence: 99%
“…The antibacterial effects of using PEI nanoparticles at 0.5, 1 and 2% by mass in a provisional cement were studied in vitro against S. mutans and Enterococcus faecalis [86]. The results indicated that the minimum effective concentration should be 1% of PEI nanoparticles to ensure a proper antibacterial activity for the dental cement [86]. Consistent results were obtained in another study, where PEI nanoparticles incorporated at a low concentration of 1% by mass in a resin composite showed a strong antibiofilm activity, and exhibited a potent broad-spectrum antibacterial activity against human salivary bacteria [87].…”
Section: Other Studies Using Nanotechnology To Tackle Oral Biofilms Andmentioning
confidence: 99%